SÍNTESE E CARACTERIZAÇÃO DA PEROVSKITA BaCe0,2Zr0,7Y0,1O3-δ PARA UTILIZAÇÃO EM CÉLULAS A COMBUSTÍVEL - Ouba, Ana Kaori de Oliveira (2016)
Solid oxide fuel cells (SOFC) are devices that convert chemical energy directly into electricity and have shown a good alternative due to its high efficiency (more than 70%) have only components solid and clean energy. Among the biggest advantages are high reliability and low emission reducing the impact on the greenhouse effect. A SOFC comprises an electrolyte and two electrodes, the cathode and the anode, and must provide substantial conductivity, above 0.1 S.cm-1. The ceramics which have excellent electrical properties are compounds based on the structure of the perovskite (ABO3), and some of these have proton and ion conduction. The objective of this study was the synthesis of a perovskite with BaCe0,2Zr0,7Y0,1O3-δcomposition and obtain a dense compound for use as an electrolyte in SOFC. The ceramic compound this composition has enhanced electrical properties, as it has proton conduction. The powders were synthesized by the modified Pechini method, and various processing routes were tested until they found the ideal containing two calcinations, a 350°C for 4 hours and another 900°C for 12 hours. After obtaining the powder were tested two types of grinds, one in vibratory mill for 6 hours and another at high energy mill for 1 hour in order to refine the particle BCZY27 and improve densification of the sample after sintering. It also used the zinc oxide, 2% and 4 mol%, as a dopant assist densification. The characterization of the post was made by X and scanning electron microscopy with EDS rays. The results showed that, as the temperature was 900C possible to obtain the desired phase containing second phases. The sintering was done at 1300°C, 1400°C and 1600°C together with milling in a vibration mill and Spex mill, with the aim of testing the best composition in each. The characterization of the sintered samples was made by X-ray diffraction, scanning electron microscopy, EDS, dilatometry, porosity and density. Impedance spectroscopy were also made to the atmospheric air and humid air at temperatures from 200 to 600°C with intervals of approximately 25°C the samples possessed apparent porosity of less than 5%. The samples sintered at 1400°C with the addition of 4 mol% of ZnO, proved to be good for the application as an electrolyte because reached full enough electrical conductivity to be used.